Prevalence and Impact of Headache in Undergraduate Students in Kirkuk University - Rebaz Ismail Ali (Kufa Journal for Nursing Sciences)
Background : Headache is one of the most common disorders of the nervous system and several of its subtypes tension-type headache, migraine, cluster headache and the so-called chronic daily headache syndromes cause substantial levels of disability for students and peoples throughout the world.